BIOFILLER VS PLATELET RICH PLASMA MESOTHERAPY IN THE TREATMENT OF PERI-ORBITAL HYPERPIGMENTATION IN PATIENTS PRESENTING TO OUTPATIENT DEPARTMENT OF DERMATOLOGY IN A TERTIARY CARE HOSPITAL-AN RCT - Sadiq, Sakina; Uzma Bashir; Ayesha Rizwan; Ayesha Anwar; Sibghatullah Rao; Shyna Shahid (Journal of Ayub Medical College Abbottabad, 2024)
Background: Peri orbital hyperpigmentation (POH) is a common presentation in dermatological outpatient departments and has multiple causes. Finding an appropriate treatment for POH can be challenging and requires case-based approach. The objective of this research was to study the effect of Biofiller Vs Platelet rich plasma meso-therapy in the treatment of Peri-orbital hyperpigmentation. Our hypothesis was Biofillers are better than platelet rich plasma therapy in the treatment of peri-orbital hyperpigmentation. It was a double-blinded randomized Control Trial (IRCT20230816059168N1) carried out in the Dermatology OPD of a tertiary care hospital in Rawalpindi over 4 months, i.e., 10.07.23 to 10.10.23. Methods: Forty-two patients meeting the inclusion criteria were included in the study after taking informed consent. Sampling was done by non-probability randomized sampling using the lottery method. 21 patients were treated with Bio fillers and another 21 by platelet rich plasma therapy (PRP). Sessions with a 2 weeks interval were done in each case and results were analyzed by peri-orbital photo-metric pigmentation scale and clinical grading improvement scale rated by a physician. Patient satisfaction and complications were also recorded. Results: Statistically significant difference in results of Group A as compared to Group B, regarding improvement in photonumeric scale, evaluation of efficacy by a blinded dermatologist and patient satisfaction i.e. p= 0.001, 0.014 and 0.001 respectively. In group A, pain was reported by 3 (14.3%), bruising by 1 (4.76%) and lumps by 2(9.5%). PRP treated group had more side effects, i.e., 9 (42.8%) reported pain, 6 (28.6%) bruising and 4 (19%) more than one complaint (p-0.001). Conclusion: Biofillers are better than PRP in the treatment of POH.